Simultaneous detection of 93 synthetic cannabinoids by liquid chromatography‐tandem mass spectrometry and retrospective application to real forensic samples. Issue 5 (12th July 2016) - Hess, Cornelius; Murach, Jacqueline; Krueger, Lynn; Scharrenbroch, Lisa; Unger, Michael; Madea, Burkhard; Sydow, Konrad
Abstract : The Internet is flooded with steadily changing synthetic cannabinoids in `Spice` products. In routine forensic work, it is difficult to keep the analytical methods for the detection of these analytes up to date. We describe a liquid chromatography‐tandem mass spectrometry method after liquid‐liquid extraction for the detection of 93 synthetic cannabinoids in human serum. The method was validated for selectivity and specificity, matrix effects, and analytical limits (<1 ng/mL for 81 substances) for qualitative analysis. A short quantitative validation regarding linearity and precision data was also conducted. The method was applied to 189 serum samples provided by police authorities. Sixty‐four samples (33.8%) were found positive for at least one synthetic cannabinoid, whereby MDMB‐CHMICA, AB‐CHMINACA, and 5 F‐PB‐22 were the substances most frequently detected. Consumption of these substances and plasma concentrations are linked to symptoms documented by the police. Six case reports are presented. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Analytical methods for the detection of currently consumed synthetic cannabinoids are difficult to keep up to date. A validated liquid chromatography tandem mass spectrometry method for the detection of 93 synthetic cannabinoids including separation of some isomers is described and applied to 64 positive forensic cases.